LY6G6D is a selectively expressed colorectal cancer antigen that can be used for targeting a therapeutic T-cell response by a T-cell engager - Corrales, Leticia; Hipp, Susanne; Martin, Katharina; Sabarth, Nicolas; Tirapu, Iñigo; Fuchs, Klaus; Thaler, Barbara; Walterskirchen, Christian; Bauer, Kathrin; Fabits, Markus; Bergmann, Michael; Binder, Carina; et al. (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) is one of the most common cancers worldwide and demands more effective treatments. We sought to identify tumor selective CRC antigens and their therapeutic potential for cytotoxic T-cell targeting by transcriptomic and immunohistochemical analysis. LY6G6D was identified as a tumor selectively expressed CRC antigen, mainly in the microsatellite stable (MSS) subtype. A specific anti LY6G6D/CD3 TcE was generated and demonstrated potent tumor cell killing and T cell activation in vitro. Ex vivo treatment of primary patient-derived CRC tumor slice cultures with the LY6G6D/CD3 TcE led to IFN secretion in LY6G6D positive tumor samples. In vivo, LY6G6D/CD3 T cell engager (TcE) monotherapy demonstrated tumor regressions in pre-clinical mouse models of engrafted human CRC tumor cells and PBMCs. Lastly, 2D and 3D cocultures of LY6G6D positive and negative cells were used to explore the bystander killing of LY6G6D negative cells after specific activation of T cells by LY6G6D positive cells. LY6G6D/CD3 TcE treatment was shown lyse target negative cells in the vicinity of target positive cells through a combined effect of IFN, TNF and Fas/FasL. In summary, LY6G6D was identified as a selectively expressed CRC antigen that can be utilized to potently re-direct and activate cytotoxic T-cells to lyse LY6G6D expressing CRC using a TcE. This effect can be spread to target negative neighboring tumor cells, potentially leading to improved therapeutic efficacy.